EVALUASI KEBIJAKAN BANTUAN LANGSUNG SEMENTARA MASYARAKAT DI KELURAHAN SAIL KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2013 - M. Syukriadi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to determine the evaluation of public policy while directassistance in the Village District of Tenayan Raya Sail Pekanbaru City in 2013.This research was conducted in the village Sail District of Tenayan RayaPekanbaru City Sail Year 2013 Sub District of Pekanbaru City Tenayan Raya in2013 are being used as research for the reason that, the village Sail District ofTenayan Raya Pekanbaru City in 2013 is getting BLSM most areas. This is adescriptive study, the data analysis techniques used are imaging techniques withwords or sentences and are split by category to obtain the data and conclusionsobtain accurate conclusions in this research. The survey results revealed that afterthe evaluation, implementation Sail BLSM in the Village District of the city ofPekanbaru Tenayan Raya Year 2013 was good, but not maximized. Theconclusion is: The implementation of the program BLSM in the Village Sail goeswell, smoothly and orderly. Phase of the program BLSM in the Village Sail startsfrom socialization, implementation of data verification RTS nomination rosters,dealing BLT, BLT disbursements, and final implementation report generation.Socialization has been implemented properly to the district level, but only a feware following up with the socialization at the RT level. BLSM card divisionprocess runs smoothly and carried out door to door to RTS. Disbursement offunds in all districts BLSM running smoothly, orderly and safe, but still thingshappen as follows: (1) the long queues and crowded at the payment location, dueto lack of payment counter, (2) RTS vulnerable (elderly, sick, and disability)mixed together, because there is no special counters for them, (3) RTS does notcome as scheduled, due to lack of socialization.Keywords: Evaluation of Public Policy, BLSM